2017
DOI: 10.3390/biom7030062
|View full text |Cite
|
Sign up to set email alerts
|

Organ–Organ Crosstalk and Alcoholic Liver Disease

Abstract: Alcohol consumption is a common custom worldwide, and the toxic effects of alcohol on several target organs are well-understood. Given the poor prognosis of treating clinically-relevant alcoholic liver disease (ALD) (i.e., alcoholic hepatitis (AH) and cirrhosis), additional research is required to develop more effective therapies. While the stages of ALD have been well-characterized, targeted therapies to prevent or reverse this process in humans are still needed. Better understanding of risk factors and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 105 publications
(112 reference statements)
0
24
0
1
Order By: Relevance
“…79 Endocrine adiponectin-FGF15/19 axis controls adipose and gut to liver communication arm of an adipose-intestine-liver partnership in response to alcohol challenges. However, other organs such as muscle, bone, spleen and brain may be within this communication axis regulated by the adiponectin-FGF15/19 axis and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…79 Endocrine adiponectin-FGF15/19 axis controls adipose and gut to liver communication arm of an adipose-intestine-liver partnership in response to alcohol challenges. However, other organs such as muscle, bone, spleen and brain may be within this communication axis regulated by the adiponectin-FGF15/19 axis and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42] No matter the etiology, chronic liver diseases share a well-documented, common natural history, which ranges initially from simple steatosis, to inflammation and necrosis (steatohepatitis), to fibrosis and cirrhosis. [43][44][45][46] Fibrosis may improve with removal of insult, but reversal of severe stages of fibrosis/cirrhosis is more limited. 47 Cirrhosis is often considered an end-stage liver disease and requires liver transplant.…”
Section: Inflammation As a Therapeutic Target For Chronic Liver Diseasementioning
confidence: 99%
“…[63][64][65] We recently demonstrated that the hepatic matrisome changes robustly to acute injury (e.g., acute lipopolysaccharide), even under conditions in which the ECM appears histologically unchanged. 45 These subhistologic transitional changes to the matrisome appear to resolve after acute injury 66,67 (►Fig. 1); with chronic injury, the transitional matrisome is replaced by collagenous scarring in the liver, which is again in-line with subcutaneous wound healing.…”
Section: Before Fibrosismentioning
confidence: 99%
“…This can be explained through the well-known classic example of hepatic encephalopathy during decompensation of chronic liver disease and alcoholic liver disease. 29 This crosstalk is linked through gut-related pathological changes such as increased permeability, altered microbiome of the gut, leading to "gut dysbiosis." 30 The brain essentially requires glucose for its metabolism which is generated in high amounts by the liver.…”
Section: Liver and Brain Crosstalkmentioning
confidence: 99%